2017
DOI: 10.1016/j.fertnstert.2017.07.293
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of elagolix treatment in women with endometriosis-associated pain: primary results from two phase 3 extension studies

Abstract: related surgery. Pharmacy costs accounted for 15.3% of total healthcare costs among endometriosis patients and 22.2% among controls. Endometriosis-related costs accounted for an average of $3,069 (22.4%) of total healthcare costs among endometriosis patients. CONCLUSIONS: Endometriosis places a significant economic and resource burden among women with Medicaid coverage. Costs and resource utilization in all measured categories were higher among patients than controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The most common adverse events were hot flushes, headache and nausea, with 25-30%, 20-22% and 12-18% of patients in the 150 mg once daily group and 52-55%, 25-29% and 15-25% of patients in the 200 mg twice daily group experiencing these symptoms, respectively. 32 The majority of hot flushes were mild to moderate with discontinuation rates for hot flushes ranging from <1% for the lower dose group to <3% for the higher dose. 33 Positive efficacy results obtained in the pivotal trials led to the approval of elagolix for the management of moderate to severe pain associated with endometriosis.…”
Section: Elagolix In Endometriosismentioning
confidence: 91%
See 4 more Smart Citations
“…The most common adverse events were hot flushes, headache and nausea, with 25-30%, 20-22% and 12-18% of patients in the 150 mg once daily group and 52-55%, 25-29% and 15-25% of patients in the 200 mg twice daily group experiencing these symptoms, respectively. 32 The majority of hot flushes were mild to moderate with discontinuation rates for hot flushes ranging from <1% for the lower dose group to <3% for the higher dose. 33 Positive efficacy results obtained in the pivotal trials led to the approval of elagolix for the management of moderate to severe pain associated with endometriosis.…”
Section: Elagolix In Endometriosismentioning
confidence: 91%
“…16 The safety and efficacy of elagolix in the treatment of endometriosis have been evaluated in four phase 2 trials, 16,[29][30][31] two phase 3 trials and two phase 3 extension studies. 32,33 The initial phase 2 trials suggested that elagolix was effective for endometriosis-related pain and associated with an adequate safety profile. 16,[29][30][31] Based on the positive results obtained in the phase 2 studies, two phase 3 trials (Elaris Endometriosis I and II (EM-I and EM-II)) were conducted to further evaluate the efficacy and safety of elagolix in women with moderate to severe endometriosisassociated pain.…”
Section: Elagolix In Endometriosismentioning
confidence: 99%
See 3 more Smart Citations